Impact of microfinance loans on the performance of SMEs: The case of Lebanon - Fida Moussa (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Microfinance is the arrangement of budgetary administrations to low-income individuals and to SMEs. An empirical study was undertaken to identify the relationship between micro credits from MFIs and the SMEs' financial performance. Secondary data were collected from 17 SMEs in North Lebanon. Another secondary data were collected from four MFIs in Lebanon concerning the characteristics of their beneficiaries. Data were analyzed using SPSS Ver. 23. The results showed notable relationships between amount of micro loan and the dependent variables, the number of women recipients of credits remains little in Lebanon, the categories of businesses mostly profiting from the MFIs in Lebanon are commerce, service, and trade sectors and the beneficiaries are primarily situated at Mount Lebanon, South, Bekaa, and at the north. The research contributes to the enduring deliberation on the effect of micro loans on the SMEs' financial performance. It is vital to see how MFIs could add to the monetary advancement of the country, by improving the welfare levels of all the needy individuals. This study can be utilized to provide useful empirical evidence for future research and to raise awareness on this significant matter for SMEs' managers, MFIs' managers and clients, and for the analysts.
Keywords: D63; O12; O43; 650; microfinance; MFIs; micro credits; micro loans; SMEs; SMEs’ performance; miniaturized scale loans